A Patient-Derived Glioblastoma Organoid Model Maintains Intertumoral and Intratumoral Heterogeneity for Therapeutic Testing. (1st September 2019) - Salinas, Ryan; Zhang, Daniel; Jacob, Fadi; Nguyen, Phuong; Sheikh, Saad; Prokop, Stefan; Dorsey, Jay F; Nasrallah, MacLean; Brem, Steven; O'Rourke, Donald M; Ming, Guo-li; Song, Hongjun
Abstract: INTRODUCTION: Glioblastoma remains invariably lethal due to its aggressive and invasive nature. It has been increasingly appreciated that molecular heterogeneity between tumors and within tumors likely contributes to the lack of efficacy of numerous clinical trials. METHODS: In order to maintain the inherent heterogeneity of glioblastoma, we employed a novel method to rapidly culture glioblastoma organoids (named GBOs) directly from neurosurgical resection. Cultures were generated from minced glioblastoma tissue in defined media free of serum, exogenous EGF/fibroblast growth factor (FGF), and matrigel so as to minimize selection bias. Over 30 GBO lines have been generated to date. Comprehensive histologic and sequencing analyses were performed to assess similarity to primary tumors. Leveraging clinical molecular and sequencing data, selected GBOs were treated with radiation/temozolamide, EGFR inhibition (gefitinib), MEK inhibition (trametinib), and mTOR inhibition (everolimus) for 7 d and analyzed by percent KI67+ cells following treatment. Gene set enrichment and gene ontology analysis was performed from pretreated sequencing data. RESULTS: Rounded GBOs form within 2 wk and maintain high similarity to the primary tumor based upon histology as well as by sequencing analysis. Treatment with radiation/temozolamide led to a decrease in the proportion of KI67+ cells in 3 of 8 tumors with some evidence of correlative clinical radiographic response. GBO response to gefitinib treatment was specific to EGFR altered tumors and enriched for EGF related gene sets. Two GBOs had downstream NF1 mutated tumors that responded to MEK inhibition with gene set enrichment for RAS signaling. Despite resistance to other experimental treatments, 1 GBO line was found to have a PI3K mutation and responded significantly to downstream mTOR inhibition. CONCLUSION: This novel culturing method of GBOs maintains both intertumoral and intratumoral heterogeneity. As clinical sequencing because increasingly prevalent, GBOs may become a valuable tool for functionally testing mutation-specific treatment strategies in a patient-specific and clinically relevant time frame.